Failure Mechanisms in Wet Tantalum Capacitors. (1976) - Hayward, D.
Abstract : The wet tantalum capacitor is well established in both power supply smoothing and timing applications and has a well proven high reliability. This paper reviews the mechanisms of the possible failures arising from mis-application or over-stressing. The effect of over voltage on the anodic oxide is considered and the influence of cathode structure on reverse voltage and ripple current capability is discussed. The silver cathode allows migration of silver ions through the electrolyte under appropriate conditions and hence produces a failure mechanism not present in the tantalum cathode device. The life of a wet tantalum unit is eventually limited by loss of water vapour leading to open-circuit. Results are presented for button style capacitors which suggest that this is in fact not a practical limitation.